Opposite regulation of XIAP and Smac/DIABLO in the rat endometrium in response to 17β-estradiol at estrus - Asselin Eric; Shooner Carl; Dery Marie-Claude; Leblanc Valerie (BMC, 2003)
Abstract During rat estrous cycle, the endometrium proliferates in response to sex steroids and specific endometrial epithelial cells undergo apoptosis in absence of embryonic factors. The central executioner of apoptosis is a family of aspartic acid-specific cysteine proteases known as caspases. Smac/DIABLO is released from the mitochondria during apoptosis and its stimulation promotes caspases activation by neutralizing members of the inhibitor of apoptosis proteins (IAPs) family, such as X-linked inhibitor of apoptosis protein (XIAP). The aim of this study was to investigate the involvement of Smac/DIABLO and XIAP in the control of caspases activation in endometrium of cycling rats. Polyoestrus female rats were sacrificed at each stage of estrous cycle (diestrus, proestrus, estrus, and metestrus). Endometrial protein extracts were collected to perform Western Blot analysis. Alternatively, uterine horns were sectioned for immunohistochemistry (IHC). We and others showed previously the presence of apoptosis at estrus in rat uterine epithelium. In the present study, cleaved caspase-3, -6, and -7 fragments were detected at estrus. IHC confirmed that caspase-3 was present only in luminal and glandular epithelium at estrus. XIAP was highly expressed at estrus in both epithelial and stromal cells. In contrast, expression of Smac/DIABLO was elevated at diestrus, proestrus and metestrus but was minimal at estrus. Treatment of ovariectomized rats with 17β-estradiol induced XIAP expression and inhibited Smac/DIABLO protein expression in the endometrium. Cleaved caspase-3, -6, and -7 fragments increased in endometrial protein extracts following 17β-estradiol treatment. Expression of NF-κB and IκB proteins, and IκB phosphorylation status were detected in the endometrium but were not influenced by the estrous cycle. These findings suggest that Smac/DIABLO and XIAP are regulated differently and may play important roles in the regulation of endometrial cell fate. Moreover, this study confirms a key role for executioner caspases in the control of apoptotic processes at estrus in the rat uterus.